1997
DOI: 10.1523/jneurosci.17-06-02181.1997
|View full text |Cite
|
Sign up to set email alerts
|

α-MSH Modulates Local and Circulating Tumor Necrosis Factor-α in Experimental Brain Inflammation

Abstract: Tumor necrosis factor (TNF-α) underlies pathological processes and functional disturbances in acute and chronic neurological disease and injury. The neuroimmunomodulatory peptide α-MSH modulates actions and production of proinflammatory cytokines including TNF-α, but there is no prior evidence that it alters TNF-α induced within the brain. To test for this potential influence of the peptide, TNF-α was induced centrally by local injection of bacterial lipopolysaccharide (LPS). α-MSH given once i.c.v. with LPS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
89
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 28 publications
(28 reference statements)
3
89
2
Order By: Relevance
“…Inflammation is reduced by α-MSH via direct and indirect mechanisms (25) (27,28 (30,31), α-MSH may be one of the therapeutic targets of CHF in the future (32,33). IL-10 is also considered to be one of the therapeutic targets for acute myocarditis and heart failure (12,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is reduced by α-MSH via direct and indirect mechanisms (25) (27,28 (30,31), α-MSH may be one of the therapeutic targets of CHF in the future (32,33). IL-10 is also considered to be one of the therapeutic targets for acute myocarditis and heart failure (12,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Yaswen et al reported that systemically administered a-MSH may contribute to central inhibition of feeding and peripheral inhibition of free fatty acid uptake as well as to stimulation of lipolysis in mice lacking proopiomelanocortin -derived peptide. 7 Elevated concentrations of a-MSH in HIV-infected patients have been reported, but circulating levels of a-MSH and their role in metabolic abnormalities associated with obesity have not as yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 aMSH has several known activities including the ability to stimulate melanogenesis, regulate body weight, and inhibit inflammation. [10][11][12][13][14][15] These effects are mediated by cell surface, G-protein-coupled, melanocortin receptors (MC-R). [16][17][18][19] aMSH binding to MC-R1 and MC-R5 activates adenyl cyclase and results in a significant increase of intracellular cAMP.…”
mentioning
confidence: 99%
“…22,23 The antiinflammatory activity of aMSH is due in part to inhibition of IkB degradation, 24,25 an effect that prevents the transcription factor nuclear factor kB (NF-kB) from entering the nucleus. NF-kB is required for the production of several pro-inflammatory factors, such as IL-1 and TNF-a 11,12,14,[26][27][28] , and has been shown to have a role in the pathogenesis of many inflammatory/autoimmune diseases. 25 The ability of aMSH to inhibit NF-kB translocation makes it an interesting target for therapeutic intervention.…”
mentioning
confidence: 99%
See 1 more Smart Citation